Organization of responsibility accounting of city electric transport enterprises’ activity - Nykyforak, Iryna; Duhanets, Nataliya; Kobrusieva, Yevheniia (Eastern-European Journal of Enterprise Technologies, 2018)
The problems of organization of responsibility accounting of the city electric transport (CET) enterprises’ activity are considered. The industry specifics of the activity of tram and trolleybus enterprises are determined. It is substantiated that the organizational and methodical structure of accounting of the CET enterprises’ activity is influenced by factors of the internal and external environment. These include state regulation of the industry, peculiarities in relations with customers, the specific nature of the products and technological peculiarities of structural units. The mathematical model of quality of service of transport enterprise customers on the basis of the verified resource efficiency indicator is developed. Such a step will allow linking the rating efficiency of transport routes with the problems of structural optimization when choosing the priorities in the maintenance of vehicles. In addition, the developed model allows evaluating the fulfillment of the route schedule, which will increase the confidence of passengers in city transport and increase passenger traffic. Thus, the proposed solution allows increasing the efficiency of passenger transport by improving the quality of service within the existing budget.